Coupled nanocomposite Co5.47N–Co3Fe7 inlaid in a tremella-like carbon framework as a highly efficient multifunctional electrocatalyst for oxygen transformation and overall water splitting. Issue 12 (18th October 2019) - Kong, Fantao; Zhang, Chaoqi; Qiao, Yu; Li, Ruijing; Kong, Aiguo; Shan, Yongkui
Abstract : A facile hydrothermal-pyrolysis strategy is proposed to prepare the coupled Co5.47 N–Co3 Fe7 /N-Cs nanocomposite as highly efficient multifunctional electrocatalyst. Abstract : Electrocatalysts with high activity, low cost and long-term durability for oxygen transformation and water splitting are highly desirable for realizing large-scale commercial application of renewable energy technologies, such as metal–air batteries and water splitting cells, but finding them remains a great challenge. Herein, a graphene/nanotube-constructed tremella-like carbon framework with 3D open aisles embedded with coupled Co5.47 N and Co3 Fe7 nanoparticles (Co5.47 N@Co3 Fe7 /N-Cs) was created via a hydrothermal–pyrolysis strategy. The mutual entanglement and connection of the nanosheets and nanotubes creates a carbon network with a hierarchically porous structure and multifarious active centers such as Fe–Co, Co(Fe)–N x moieties and nitrogen-doped carbon (N-C) co-existing on the surface of the prepared Co5.47 N@Co3 Fe7 /N-Cs, exhibiting excellent trifunctional electrocatalytic performance for the ORR, OER and HER. A primary zinc–air battery assembled with Co5.47 N@Co3 Fe7 /N-C-900 gains an advantage over its Pt/C-based counterparts. Besides, the performance of an overall water splitting device using Co5.47 N@Co3 Fe7 /N-C-900 as the electrode material is comparable to that of a Pt/C–IrO2 pair-assembled cell. To the best of our knowledge, this is a top-notch trifunctional electrocatalyst for the ORR, HER and OER in comparison to those reported so far. This work provides an effective strategy to prepare high-performance trifunctional electrocatalysts with excellent catalytic performance and wide application prospects in the sustainable energy conversion field.